Improving Perceived Accuracy for In-Car Media Search - Ju, Y. C.; Seltzer, Mike; Tashev, Ivan (International Speech Communication Association, 2009)
Speech recognition technology is prone to mistakes, but this is not the only source of errors that cause speech recognition systems to fail; sometimes the user simply does not utter the command correctly. Usually, user mistakes are not considered when a system is designed and evaluated. This creates a gap between the claimed accuracy of the system and the actual accuracy perceived by the users. We address this issue quantitatively in our in-car infotainment media search task and propose expanding the capability of voice command to accommodate user mistakes while retaining a high percentage of the performance for queries with correct syntax. As a result, failures caused by user mistakes were reduced by an absolute 70% at the cost of a drop in accuracy of only 0.28%.